Public internet access in areas of deprivation: The case of Glasgow - Gillian Anderson; Jason Whalley (International Telecommunications Society (ITS), 2013)
The Internet plays an increasingly central role in the lives of individuals. Through the Internet, individuals can engage in a wide array of activities such as shopping, participating in social networking activities, obtaining information and so forth. Given the extent to which the Internet is now used, those without access are placed at a disadvantage. They will miss out on the savings that occur when you shop online, lose contact with friends and family by not engaging in social networking and lack information on which to make decisions. This paper explores the role that libraries may play in providing Internet access. This is examined within the context of Glasgow, a large post-industrial city where Internet adoption is lower than in comparable cities and which has a large proportion of its population facing a range of socio-economic hardships. Primary data was collected, from library staff across the city and users in three areas of deprivation. The analysis demonstrates the role played by libraries as the provider of public Internet access. It also shows that this role is not without its difficulties - inadequate levels of resources have been provided to fulfil the multiple roles played by libraries in these communities. The data highlights the wide range of activities that users undertake online. In addition, the analysis shows how government policies shape the scope and quality of the infrastructure that is available while encouraging further use of the Internet in libraries.
Keywords: 330; Glasgow; libraries; Internet access